Detection of circulating HPV16 DNA as a biomarker in the blood of patients with human papillomavirus‐positive oropharyngeal squamous cell carcinoma. Issue 3 (19th December 2018) - Mazurek, Agnieszka M.; Rutkowski, Tomasz; Śnietura, Mirosław; Pigłowski, Wojciech; Suwiński, Rafał; Składowski, Krzysztof
Abstract: Background: Development of biomarker analysis using the circulating cell‐free DNA (cfDNA) methodology is a challenge for noninvasive cancer diagnosis. In this study, a comparison between the plasma and tumor tissue HPV16 DNA viral loads (VLs) has been presented. Methods: Real‐time polymerase chain reaction was performed for quantitating of HPV16 DNA in the plasma and tumor samples of patients with oropharyngeal cancer. Results: Among the tissues, HPV16‐positive patients with oropharyngeal squamous cell carcinoma, nonsmoking patients, displayed significantly higher HPV16 DNA VLs in their tissue. No smoking and advanced N disease were the most important predictors for cHPV16 DNA (circulating HPV16 DNA) detection. The cHPV16‐positive women displayed significantly higher VLs in their tumor tissues compared to the men, although without notable impact on the blood detection. Conclusions: Many factors were responsible for human papillomavirus DNA circulation in blood. As a result of the small size of the analyzed group, some observed discrepancies need to be proven on a larger cohort.